Development of the system to control milk acidity in the milk pipeline of a milking robot - Nanka, Oleksandr; Shigimaga, Viktor; Paliy, Andriy; Sementsov, Vitaliy; Paliy, Anatoliy (Eastern-European Journal of Enterprise Technologies, 2018)
Acidity characterizes the suitability of milk for primary processing and is one of the key parameters monitored when accepting it at a dairy plant. Therefore, it is important to timely separate milk with lowered acidity in the process of milking by a robot. However, no technical means for the detection and separation of milk with lowered acidity in a milk pipeline were designed for robotic milking systems. Based on the results of experimental study, we established a linear correlation dependence of milk acidity, using a traditional Turner method, on pH. We calculated parameters for the main and additional containers, for milk of superior grade and for non-standard milk in terms of acidity. Linear parameters are determined for inserting into the main milk pipeline of a robot the measuring pH-electrode and a tee with electromagnetic valve for the automated discharge of non-standard milk. Based on the experimental study and our calculations, we developed a project of the technical system for the robotic cow milking technology. A standard technology is complemented by a process of automated measurement of milk pH in a flow, which is implemented using a high-speed transistor pH-FT electrode with a measuring unit. Control over milk pH in a flow during milking makes it possible to operatively solve two tasks at a time ‒ to improve the accuracy of estimating the quality of starting raw materials and to correct the feed of cows in order to standardize the acidity of milk required for its acceptance at a milk processing plant. We thus exclude a labor-intensive laboratory operation for determining the acidity because this indicator has already been measured during robotic milking process. Therefore, our improvement of technology for robotic milking will make it possible to more accurately assess the quality of raw milk using milking robots that are included in the system of machines for precision cattle breeding.